2019
DOI: 10.1108/jsit-06-2018-0091
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect acceptance and use of information systems within the Maritime industry in developing countries

Abstract: Purpose Although information and communication technology has become a significant driver for organizational efficiency and effectiveness, there is inadequate empirical research on technology acceptance in the maritime industry especially in developing countries. Literature on how behavior and attitude influence technology acceptance is non-existent. This study therefore aims to augment existing literature on technology acceptance in developing countries with particular emphasis on the maritime industry. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 81 publications
4
20
0
Order By: Relevance
“…This research result is supported by other research such as Hossain and Wiafe et al (Md. A. Hossain, 2019;Wiafe et al, 2019), where there is no positive significance between effort expectancy and behavior intention. (Eneizan et al, 2019;Khalilzadeh et al, 2017;Mohd Thas Thaker et al, 2021;Musyaffi, 2020;Rahi & Abd.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This research result is supported by other research such as Hossain and Wiafe et al (Md. A. Hossain, 2019;Wiafe et al, 2019), where there is no positive significance between effort expectancy and behavior intention. (Eneizan et al, 2019;Khalilzadeh et al, 2017;Mohd Thas Thaker et al, 2021;Musyaffi, 2020;Rahi & Abd.…”
Section: Discussionsupporting
confidence: 85%
“…Hossain, 2019). And the results are not significant regarding effort expectancy in the field of maritime information systems (Wiafe et al, 2019) and mobile payment (Md. A.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The theory of planned behaviour (Ajzen, 1991) explains that attitude influences behaviour. Also, findings from Wiafe et al (2019) confirm this relationship. However, some scholars have argued otherwise (Festinger, 1962;Harmon-Jones and Harmon-Jones, 2007;Wiafe et al, 2014), they all agree that there is a relationship between attitude and behaviour.…”
Section: Attitude Towards Compliance and Compliance Intentionsupporting
confidence: 54%
“…It is an undisputable fact that greater productivity will be enhanced from using the PPS since intention to use and actual usage behavior will be extremely high under the PPS. Scholars such as (Wiafe et al, 2019;Venkatesh, Morris and Davis, 2003;Venkatesh and Davis, 2000;Davis, et al, 1989) have all shown in their respective work that the perceived usefulness variable is a stronger predictor of intention to use a new system in both mandatory and voluntary environments. The PPS is operated in a mandatory environment, subsequently based on the arguments advanced above the hypotheses related to the PU variable is posited as: H1.…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%